Sistem Informasi Manajemen Aplikasi Pengarsipan Data Berbasis Web Pada Perusahaan - Agung Wijoyo; Muhammad Fauzan; Farhan Fadhillah; Hasbi Pandiani; Wizri Fauzi Arif (Router : Jurnal Teknik Informatika dan Terapan, 2024)
Technology has undergone significant and rapid change with the transition from self-managed data centers to visualized infrastructure. Data archiving has a very important role because it can make it easier to process data quickly and accurately. Web-based information systems have become an integral part of digital transformation in various industrial sectors. By providing centralized access to computing resources, data storage, and applications over the internet, the cloud provides significant freedom and flexibility. Web-based information systems bring great benefits to organizations that successfully adopt them. While challenges such as security and regulatory compliance need to be overcome, the opportunities for innovation and operational efficiency make cloud-based information systems a strategic choice in a company's digital transformation roadmap. Several institutional companies and individuals have used web-based archiving but it has not been effective. For this reason, a good archiving system is needed that makes it easier to search and process data. Web-Based Archiving Management Information System which will provide convenience in processing data to be more effective and accurate. Apart from that, it can also save time and better manage reports and decision making within the Company.